Making strange : beauty, sublimity, and the (post)modern "third aesthetic". - Grabes, Herbert (Amsterdam : Rodopi, 2008)
The aesthetic of the strange -- The strange art and literature of modernism -- The strange art and literature of postmodernism -- The aesthetic of the strange as the aesthetic of modernism and postmodernism -- Theoretical foundations of the aesthetic of the strange.
English translation by Marc Colavincenzo from Einführung in die Literatur und Kunst der Moderne und Postmoderne : die Ästhetik des Fremden (Tübingen & Basel: Francke, 2004), with further editing by Gordon Collier
boek